Reflections on Working with Communities and Community-Based Projects in Bangladesh - Rahman, M.; Pokrant, Bob (Springer, 2014)
Community-based studies are a central feature of current development and clim ate change research and planning in developing countries. In this chapter we reflect upon our engagement with place-based communities over two decades in rural Bangladesh. We draw upon several encounters with local communities to illustrate the relationship between communities of practice and of place; com- plexities of putting what local people say and do at the centre of project work; the relationship of policy to practice; the difficulties of balancing immediate gains with longer term sustainability; and the need to locate place-based communities within wider ecological, economic and political networks of activity and influence to ensure more effective planning.